Weight age factor for Malaysia green highway assessment - Ismail, Mohd. Affendi (2013)
A green highway is an effort to achieve sustainable approach for sustainable infrastructure. Key requirements for realizing green highway goals comprise of the fulfilment of Green Highway Index (GHI). GHI development and establishment of its criteria provide alternative and appropriate options for highway assessments. The weightage factors help to set the priorities of green highway elements according to their numbering value. The aim of this research is to establish weightage factors for the green highway criteria to be used in the Malaysia Green Highway assessment. An extensive literature review was undertaken on five major criteria identified in the Malaysia green highways assessment which are Sustainable Design and Construction Activities (SDCA), Energy Efficiency (EE), Material and Technology (MT), Environmental and Water Management (EWM), and Social and Safety (SS). In overall, 133 variables were selected from five main criteria to run the weightage Factor Analysis of Malaysia Green Highway Assessment. The elements were confirmed by 140 respondents, participating in questionnaire surveys, and were analysed using SPSS 18.0. A pilot analysis was undertaken by the reductions of factors to select a number that was easy to analyse but explained most of the variance using Factor Analysis. Factor score was calculated for each variable by multiplying the mean value of criterion with respective Factor Loading. The calculation of weightage factor was done by determining the ratio of percentage of population over the percentage of sample in a main criterion. Criterion with higher weightage was considered more important than another. Out of 133 criteria, 7 criteria were chosen for SDCA: 4 for EWM, another 4 for MT, 6 for EE and 7 for SS. The results show that all of these five main criteria served as essential basis for the development of Malaysia Green Highway Assessment